Factor structure and psychometric properties of the Persian versions of the Pediatric Daytime Sleepiness Scale and Morningness-Eveningness Scale for Children - Ali Nouri; Fattaneh Esmaeili; Heliya Seyedi; Sahba Rezaeian; Sareh Panjeh; Hugo Cogo-Moreira; Sabine Pompeia (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The Pediatric Daytime Sleepiness Scale (PDSS) and the Morningness-Eveningness Scale for Children (MESC) are widely used to measure two important facets of sleep patterns, but neither have been adapted and validated for use in Iran. The purpose of this study was to examine the psychometric properties and factor structure of the Persian versions of the PDSS and the MESC in a sample of Iranian adolescents. MATERIALS AND METHODS: The Persian versions of PDSS and MESC were translated and administered to a representative sample (n = 407) of Iranian early adolescents, aged 9-15 years, who attended school in morning shifts. The factor structure of both scales, found in prior studies, was tested using Confirmatory Factor Analyses to assess their validity and reliability. RESULTS: The results revealed that the model fit indices of the one factor solution of the PDSS and the two factor solution of the MESC were acceptable to good. A high Pearson correlation was found between raw and latent factor scores for the PDSS and the two factors derived from the MESC (i.e., Morningness and Planning). Furthermore, the higher the PDSS score (more daytime sleepiness), the lower the MESC scores (more eveningness), indicating criterion validity of the scales showing the expected increase in daytime sleepiness in evening oriented adolescents who wake up early for attending school. CONCLUSION: The Persian versions of the PDSS and the MESC can be considered reliable and valid tools for evaluating, respectively, daytime sleepiness and morningness-eveningness in the adolescent population of Iran.